ANALYSIS OF FOREIGN TOURIST DYNAMICS ON THE PERFORMANCE OF LOCAL ORIGINAL INCOME OF BALI PROVINCE IN THE ERA OF SUSTAINABLE RECOVERY (2019-2024) - Nur Zaskia Andriani Safira; Safila Fidrianata; Eva Hany Fanida; Revienda Anita Fitrie (Journal Informatic, Education and Management (JIEM), 2026)
The tourism sector is the backbone of the Bali Province economy , contributing significantly to Regional Original Income (PAD). This study aims to analyze the relationship between the dynamics of foreign tourist visits and the performance of Bali Province's PAD in the 2019-2024 period , which includes three distinct phases : pre-pandemic stability , extreme contraction due to the COVID-19 pandemic , and sustained recovery . The study uses a descriptive qualitative approach with case study methods and thematic analysis . Secondary data were obtained from the Statistics Indonesia (BPS) of Bali Province , the Directorate General of Taxes (DJPb) of the Ministry of Finance of Bali Province , the Directorate General of Taxes (DJPPK) of the Ministry of Finance , and accredited national journals . The results show that the dynamics of foreign tourist visits have a consistent and direct relationship with the performance of Bali's PAD, which operates primarily through local taxes from the accommodation and food and beverage sectors . The analysis of the three temporal phases reveals an asymmetric pattern , namely that the contraction of tourism due to the COVID-19 pandemic resulted in very significant fiscal pressure . However , the recovery that has taken place since 2022 has proven to exceed pre-pandemic levels in 2024. This study offers novelty with a three- phase temporal analysis approach that allows for the contextual identification of tourism transmission mechanisms to PAD . The results can provide an empirical basis for recommendations for diversifying the PAD base as a long - term regional fiscal vulnerability mitigation strategy .